PERAN YURISPRUDENSI MAHKAMAH AGUNG DALAM MEMBENTUK KEPASTIAN HUKUM DAN KONSISTENSI PUTUSAN DI INDONESIA: STUDI KEPUSTAKAAN - Gunawan Widjaja; Cecep Suhardiman (JOURNAL OF LAW AND NATION, 2025)
This study discusses the important role of Supreme Court jurisprudence in establishing legal certainty and consistency of decisions in the Indonesian judicial system. Although the Indonesian legal system emphasises written sources of law, the emergence and application of jurisprudence has become increasingly significant, especially in overcoming legal ambiguities and gaps resulting from inadequate regulations in legislation. By providing interpretative guidelines and practical standards, Supreme Court decisions serve as persuasive references for lower courts, thereby minimising disparity in rulings and enhancing the predictability of case outcomes. This study highlights how the utilisation of jurisprudence not only strengthens public trust in the judicial system but also contributes to the integrity and legitimacy of court decisions. However, challenges remain, such as limited access to relevant decisions and uneven understanding among judges. Therefore, sustained efforts—including the digitisation of decisions and regular training—are needed to optimise the function of jurisprudence in achieving legal certainty and consistency in Indonesia.